Macrofauna bentónica asociada a bancos ostrícolas en las lagunas costeras Carmen, Machona y Mecoacán, Tabasco, México - Susan Tepetlan, P.V. (2008)
Oyster beds have an important impact on coastal ecosystems. In this work, samplings were done during the dry, the rainy and the “North wind” seasons, in eight oyster reefs at the Lagoons of Mecoacán, Carmen and Machona, in Tabasco, Mexico. The α diversity was calculated with the Shannon-Wiener, Simpson and Margalef indexes. An Analysis of Variance was done to evaluate if there was a difference in the average of the indexes at each reef in every season, verifying the assumptions of normality and variance homogeneity. In the case of mollusk richness, we found 13 families, 13 genera and 15 species of gastropods, as well as 8 families, 10 genera and 11 species of bivalves. Seven families, 11 genera and 12 species of crustaceans were recorded. In the case of mollusks, the highest average value of species richness was recorded during the dry season, in Puente de Ostión reef (DMg= 13.6), whereas in the case of species diversity, the highest average value was recorded during the “North wind” season, at Largo (H’ = 0.77). The dominant mollusks during the three seasons were Ischadium recurvum, Isognomon alatus and Crepidula plana. In the case of crustaceans, the highest average value, both in species richness and diversity, was recorded during the rainy season (DMg= 15.50, H’ = 1.15) at Pinzón reef. The dominant crustaceans were Balanus eburneus, Balanus improvisus, Eurypanopeus depressusand Petrolishtes armatus.